2009
DOI: 10.1088/1741-2560/6/2/026006
|View full text |Cite
|
Sign up to set email alerts
|

Functional localization and visualization of the subthalamic nucleus from microelectrode recordings acquired during DBS surgery with unsupervised machine learning

Abstract: Microelectrode recordings are a useful adjunctive method for subthalamic nucleus localization during deep brain stimulation surgery for Parkinson's disease. Attempts to quantitate and standardize this process, using single computational measures of neural activity, have been limited by variability in patient neurophysiology and recording conditions. Investigators have suggested that a multi-feature approach may be necessary for automated approaches to perform within acceptable clinical standards. We present a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
72
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 27 publications
2
72
0
4
Order By: Relevance
“…We used a 4-second duration for T, and the following lengths for D: 0.025, 0.05, 0.075, 0.1, 0.15, and 0.2 mm. Our value for T was based on observations that indicated that this duration provides an empirically optimal trade-off between increased spatial resolution and feature stability at the electrode velocities we typically employed ( [14] , data not shown). For each window, we used the time and depth at the temporal center of the window as the time and depth stamp.…”
Section: Feature Extraction From Sliding Time and Depth Windowsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used a 4-second duration for T, and the following lengths for D: 0.025, 0.05, 0.075, 0.1, 0.15, and 0.2 mm. Our value for T was based on observations that indicated that this duration provides an empirically optimal trade-off between increased spatial resolution and feature stability at the electrode velocities we typically employed ( [14] , data not shown). For each window, we used the time and depth at the temporal center of the window as the time and depth stamp.…”
Section: Feature Extraction From Sliding Time and Depth Windowsmentioning
confidence: 99%
“…The computational features used here were reported previously [14,16] . We made a slight modification by normalizing each feature to the data window length (e.g.…”
Section: Feature Extraction From Sliding Time and Depth Windowsmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, MER signals are observed both visually and with audio by the physiologist and/or neurosurgeon during surgery to identify the functional targets. Recently, several studies have shown that MER data can be utilized for automatic localization of the STN with reduced variation and better accuracy [25,26,27,28,29,30]. Commonly used signal features include the background noise level, spike count and power spectral density (PSD) in the beta and theta (tremor) frequency bands.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of targeting errors to DBS necessitates the use of some form of intraoperative neurophysiologic monitoring to confirm the correct targeting during surgery. The purpose of the development of numerical techniques to MER processing is to assist the surgical team in determining the optimal location of the lesion or DBS lead [2][3][4].…”
Section: Introductionmentioning
confidence: 99%